PENGARUH MANAJEMEN LABA, KEPEMILIKAN MANAJERIAL, DAN UKURAN PERUSAHAAN TERHADAP CORPORATE SOCIAL REPORTING (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia) - Zulaikha, Zulaikha (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2014)
This research aims to examine the influence of earnings management, managerial ownerships,and firm size on the corporate social responsibility disclosures. The samples of Â this study aremanufacturing firms listed in the Indonesia Stock Exchange in 2009-2011. The results showthat the managerial ownership and firm size significantly affect corporate social responsibilitydisclosures, however, eranings management does not. Based on the legitimacy theory, thesefindings support that the more managerial ownership and firm size so it will the more corporatesocial responsibility disclosures.